The Antecedents of Student Entrepreneurial Performance: Examining Human Resource Empowerment and Dynamic Capabilities - Utami, Indah; Osman, Sharina; Dhini, Berliana; Gimnastiar, Muhamad (LifeSciFi, 2023)
Performance is the set of results achieved and refers to the act of accomplishing and carrying out a job or task as requested. The purpose of this study is to examine how the study of human resource (HR) empowerment and dynamic capabilities can enhance entrepreneurial performance. The research plan encompasses collecting relevant national and international journals, constructing a conceptual framework and research title, and subsequently preparing proposals in accordance with the specified provisions. The implementation stage includes the preparation of instruments, data collection, questionnaires, and data analysis. Finally, the reporting stage results in the publication of scientific articles. The research method employed tested the validity and reliability of the direct and indirect influence of independent variables, belief systems, and human resource empowerment on the performance of student entrepreneurs. The analysis tool utilized was a statistical test employing SPSS version 18.0, complemented by SMART PLS version 4.0. Sampling was conducted through random sampling from the population of all student entrepreneurs in Kuala Lumpur, Malaysia, with a sample size of 100 respondents. The study's findings indicate that dynamic capabilities and human resource empowerment have a positive influence on increasing student entrepreneurship in Chow Kit, Kuala Lumpur.